Kesiapan Guru Ekonomi Menghadapi Pembelajaran Tatap Muka Pada Pandemi Covid-19 - Metha Lubis; Fika Rahmanita; Putra Pardamean Nauli (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2021)
The aim of this study is to det was conducted to see if schools and economic teachers were ready to host face-to-face classes during the COVID 19 pandemic. This type of research is descriptive and uses qualitative data. The data from this survey was obtained through in-depth interviews with respondents or informants. In this study, the informants were, in particular, the principal, vice-principal, and teacher of the Economics and Social Sciences. The data used by researchers in this study was obtained through data collection techniques in the form of observations, interviews, and documentation. The lessons learned from this study prepare schools and economic educators to face face-to-face learning discourse during the COVID 19 pandemic, including the application of health protocols in line with government-established guidelines, Central and local governments.